Siloxane compositions and uses thereof

Through the combination of organopolysiloxane and platinum-based catalyst of a specific ratio, the high extension fracture rate and adhesion of silicon rubber are achieved, solving the problem of bubbles or peeling of existing silicon rubbers under negative pressure environments, and maintaining stability under high temperature conditions.

JP7661508B2Active Publication Date: 2025-04-14WACKER CHEMIE AG
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023547815
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-09
Publication Date
2025-04-14
Estimated Expiration
2041-02-09

AI Technical Summary

Technical Problem

Existing silicone rubber compositions are prone to bubbles or peeling under negative pressure environments, and their hardness increases will lead to a reduced rate of extension fracture and adhesion, affecting display packaging or optical bonding applications.

Method used

The -crosslinking of silicon rubber is achieved through addition reaction by using an organic polysiloxane composition of specific ratios, including organopolysiloxanes at both ends of Silicon-bonded alkenyl groups, organopolysiloxanes in Silicon-bonded hydrogen atoms, and platinum-based catalyst.

Benefits of technology

The extension fracture rate and adhesion of silicone rubber are improved, while maintaining good stability under high temperature and negative pressure conditions to avoid bubbles or peeling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661508000004
    Figure 0007661508000004
  • Figure 0007661508000001
    Figure 0007661508000001
  • Figure 0007661508000002
    Figure 0007661508000002
Patent Text Reader

Abstract

Disclosed is a siloxane composition, comprising: (a) at least one organopolysiloxane, each molecule of which contains two alkenyl groups bonded to silicon atoms at both ends of the chain; (b) at least one organopolysiloxane, each molecule of which contains at least three alkenyl groups bonded to silicon atoms; (c) at least one organopolysiloxane, each molecule of which contains two hydrogen atoms bonded to silicon atoms at both ends of the chain; and (d) at least one hydrosilylation catalyst, with the proviso that component (c) is used in an amount of 30% by weight or more based on the total weight of the composition, and the composition comprises, each molecule of which contains 0.01% by weight or less of component (e) at least one organopolysiloxane, each molecule of which contains at least three hydrogen atoms bonded to silicon atoms.The silicone gel cured therefrom has moderately low permeability, higher elongation at break, better gel adhesion, and excellent resistance to high temperature and negative pressure.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to siloxane compositions and uses thereof. [Background technology]

[0002] Silicone gel compositions are typically addition reaction curable organopolysiloxane compositions that include: i) an organopolysiloxane as a base polymer having at least two silicon-bonded alkenyl groups, such as vinyl groups; ii) an organohydrogenpolysiloxane as a crosslinker having at least three silicon-bonded hydrogen atoms (i.e., Si-H groups); and iii) a platinum-based catalyst that produces a cured product via the addition reaction of the Si-H groups to the alkenyl groups.

[0003] The cured product of conventional silicone gel composition usually has a high penetration value (i.e., very soft), which means that when these silicone gels are placed under negative pressure environment, such as at high altitude, they will inevitably cause undesirable bubbles or peeling caused by low gel strength.Increasing the hardness of the cured gel is used to alleviate the problem.However, higher hardness of the cured gel usually results in reduced breaking elongation and reduced adhesion, which affects the application of display potting or optical bonding.

[0004] Silicone gel compositions using vinyl MQ silicone resin as a crosslinker have also been reported. EP1737504B discloses a silicone gel composition containing 100 parts by weight of vinyl-terminated polydimethylsiloxane with a viscosity of 400 mPa·s, 44 parts by weight of vinyl MQ silicone resin, 18 parts by weight of hydrogen-terminated polydimethylsiloxane with a viscosity of 15 mPa·s, and 0.01% platinum-based catalyst. However, such silicone gel still has a higher penetration value of 135, which is not suitable for use in negative pressure environments due to the occurrence of bubbles or peeling. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] European Patent No. 1737504 Summary of the Invention

[0006] In view of the existing problems, the present disclosure provides a siloxane composition and a silicone gel cured therefrom that has suitable low permeability and exhibits at least one or more of the following properties: 1) Higher elongation at break and better resistance to deformation and tension compared to existing gels with the same penetration value; 2) Better gel adhesion; 3) The gel has excellent heat resistance and does not bubble or peel off even when exposed to a temperature of 95°C for 200 hours. 4) Even when the gel is exposed to a negative pressure of -1 atmosphere for three days, it has excellent resistance to negative pressure and no bubbles or peeling occurs.

[0007] There are two reasons why bubbles or peeling occurs. One is that some invisible bubbles in the gel expand rapidly at high temperature or negative pressure, which will result in visible expanded bubbles or cause peeling or cracking if the strength of the gel is not high enough. The other is that the gel supporting substrate warps at high temperature or negative pressure, which will cause the gel to separate and peel or crack if the gel strength is low.

[0008] As used herein, "silicone gel" refers to a cured product that has a low crosslink density, is composed mainly of organopolysiloxane, and has a penetration value according to ASTM D1403 (1 / 4 cone) of 20 to 200. This corresponds to a product that has a measured value (rubber hardness value) of zero in a rubber hardness measurement performed according to GB / T531-1999, and has a hardness that is sufficiently low to not exhibit a valid rubber hardness value.

[0009] The term "penetration" as used herein refers to the depth to which a standard cone will freely fall into a gel sample under a specific load for a specific time. The greater the penetration, the softer the gel and the lower its mechanical strength. The penetration value of a silicone gel can also be used to characterize its crosslink density, since the mechanical strength of a silicone gel increases with increasing crosslink density and the penetration decreases with decreasing crosslink density. The higher the penetration value, the lower the crosslink density.

[0010] As used herein, "silicone rubber" refers to a cured product that is based on organopolysiloxane and that exhibits a valid rubber hardness value when the rubber hardness value is measured according to GB / T531-1999 and exceeds zero.

[0011] In this specification, the term "tackiness" refers to the property of a material that is sticky to the touch but does not adhere to other materials to a significant degree, and is essentially different from "adhesion". "Adhesion" refers to the property of a material that adheres to other materials, such as substrates, by typical chemical action, and adhesive strength is usually used to evaluate adhesion. In addition, adhesion is irreversible, and the material cannot adhere to other materials again when peeled from it. However, a material with tackiness sticks to other materials by typical physical action, and adhesion is reversible, and the material can adhere to other materials again when peeled from it.

[0012] In this specification, "viscosity" is measured according to conventional methods in the art, unless otherwise specified.

[0013] The first aspect of the present disclosure is as follows: (a) at least one organopolysiloxane containing, at each chain end, two alkenyl groups bonded to silicon atoms per molecule; (b) at least one organopolysiloxane containing at least three alkenyl groups bonded to silicon atoms per molecule; (c) at least one organopolysiloxane containing, at each chain end, two hydrogen atoms bonded to silicon atoms per molecule; and (d) at least one hydrosilylation catalyst; with the proviso that component (c) is used in an amount of 30 weight percent or more, preferably 40 weight percent or more, based on the total weight of the composition, and with the proviso that component (e) contains 0.01 weight percent or less, based on the total weight of the composition, of at least one organopolysiloxane containing at least three hydrogen atoms bonded to silicon atoms per molecule.

[0014] <Component (a)> Organopolysiloxanes (a) are well known in the art. Alkenyl groups are attached to silicon atoms at both ends of the chain, and the remaining groups attached to the silicon atoms are each independently selected from monovalent organic groups free of aliphatic unsaturation.

[0015] The organopolysiloxane (a) is typically linear. Some exemplary polyorganosiloxanes (a) can be described by the following formula: R 1 R 2 2SiO(R 2 2SiO) m SiR 2 2R 1 In the formula, R 1 is independently in each occurrence an alkenyl group having 2 to 6 carbon atoms, e.g., vinyl, allyl, propenyl, butenyl, hexenyl, preferably vinyl, allyl and propenyl, more preferably vinyl; R 2is independently in each occurrence a substituted or unsubstituted monovalent organic radical, in particular a monovalent hydrocarbon radical having 1 to 20, preferably 1 to 10, carbon atoms, for example alkyl, such as methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl, aryl or alkaryl, such as phenyl, tolyl, xylyl, mesityl, ethylphenyl, benzyl, naphthyl, and halogenated or organic group functionalized derivatives of the above radicals, such as 3,3,3-trifluoropropyl, o-, p- and m-chlorophenyl, aminopropyl, 3-isocyanatopropyl, cyanoethyl, preferably methyl and phenyl, more preferably methyl; m is a positive number such that organopolysiloxane (a) has a dynamic viscosity at 25° C. of 100 to 50,000 mPa·s, for example, 200 to 20,000 mPa·s, in particular 500 to 10,000 mPa·s.

[0016] Component (a) of the present disclosure may be a single alkenyl-terminated organopolysiloxane or a mixture of different alkenyl-terminated organopolysiloxanes differing in molecular structure (e.g., type and number of substituents) or viscosity. For a mixture of organopolysiloxanes, m represents an average value and the viscosity range filled by m is for the viscosity of the mixture.

[0017] Generally, silicone compositions used as potting materials are required to have lower viscosities, and correspondingly, the viscosity of the alkenyl-terminated organopolysiloxane is usually low. However, it is preferred to incorporate a small amount of a high-viscosity alkenyl-terminated organopolysiloxane into component (a) in order to reduce the crosslink density and obtain a silicone gel with higher elongation at break, better adhesion and lower permeability.

[0018] In one embodiment of the present specification, component (a) includes (a1) an organopolysiloxane having two alkenyl groups bonded to silicon atoms per molecule at both ends of its chain, and having a dynamic viscosity at 25° C. of 100 mPa·s or more and less than 5000 mPa·s, and (a2) an organopolysiloxane having two alkenyl groups bonded to silicon atoms per molecule at both ends of its chain, and having a dynamic viscosity at 25° C. of 5,000 mPa·s or more and 50,000 mPa·s or less. According to the above embodiment, component (a2) is suitably used in an amount of 2% by weight to 20% by weight, for example 5% by weight to 15% by weight, based on the total weight of composition (a), and the ratio of the number of moles of alkenyl groups provided by component (a1) to the number of moles of alkenyl groups provided by component (a2) is preferably (10-50):1.

[0019] In the present disclosure, component (a) is suitably used in an amount of 20% to 70% by weight, for example 35% to 55% by weight, based on the total weight of the composition.

[0020] <Component (b)> The organopolysiloxane as component (b) acting as a crosslinker is different from the organopolysiloxane as component (a). The polyorganosiloxane (b) can be linear, branched or resinous. The linear polyorganosiloxane (b) is typically R 2 3SiO 1 / 2 , R 1 R 2 SiO 2 / 2 , R 1 R 2 2SiO 1 / 2 and R 2 2SiO 2 / 2 (In the formula, R 1 and R 2 The branched or resinous polyorganosiloxane (b) is composed of units selected from trifunctional units, such as R 1 SiO 3 / 2 and R 2 SiO 3 / 2 and / or tetrafunctional units, e.g., SiO 4 / 2 (In the formula, R 1 and R2 is as defined above.

[0021] Some exemplary polyorganosiloxanes (b) are (b1) essentially R 1 R 2 2SiO 1 / 2 Units and SiO 4 / 2 (b2) an organopolysiloxane consisting essentially of R 2 3SiO 1 / 2 Units and R 1 R 2 SiO 2 / 2 (b3) an organopolysiloxane consisting essentially of R 1 R 2 2SiO 1 / 2 Units, R 1 R 2 SiO 2 / 2 Units and R 2 2SiO 2 / 2 (b4) an organopolysiloxane consisting essentially of R 1 R 2 2SiO 1 / 2 , R 2 2SiO 2 / 2 Units and R 2 SiO 3 / 2 Units (wherein R 1 and R 2 is as defined above. By "essentially" in this specification, it is meant that the polyorganosiloxane (b) contains at least 80 mol %, such as at least 90 mol %, or even at least 95 mol % of the above-listed units.

[0022] In the present disclosure, polyorganosiloxane (b1) is particularly preferred, R 1 R 2 2SiO 1 / 2 Units and SiO 4 / 2 The molar ratio of the unit is suitably in the range of (0.4-1):1, for example (0.5-0.9):1.

[0023] Component (b) is suitably used in an amount of from 1% to 10% by weight, for example from 2% to 8% by weight, based on the total weight of the composition.

[0024] <Ingredient (c)> Component (c) is used as a chain extender. Component (c) preferably has a dynamic viscosity at 25° C. of 30 mPa·s or more and less than 1,000 mPa·s.

[0025] The organopolysiloxane (c) is typically linear. Some exemplary polyorganosiloxanes (c) can be described by the following formula: HR 2 2SiO(R 2 2SiO) n SiR 2 2H In the formula, R 2 is as defined above, n is a positive number, and the organopolysiloxane (c) has a dynamic viscosity at 25°C of 30 mPa·s or more and less than 1,000 mPa·s.

[0026] Component (c) of the present disclosure may be a single hydrogen-terminated organopolysiloxane or a mixture of different hydrogen-terminated organopolysiloxanes differing in molecular structure (e.g., type and number of substituents) or viscosity. For a mixture of organopolysiloxanes, n represents an average value and the viscosity range filled by n is for the viscosity of the mixture.

[0027] In order to obtain a silicone gel having better adhesion and lower permeability, component (c) of the present disclosure preferably comprises (c1) an organopolysiloxane containing two hydrogen atoms bonded to silicon atoms per molecule at both ends of its chain, and having a dynamic viscosity at 25° C. of 30 mPa·s or more and 200 mPa·s or less, and (c2) an organopolysiloxane containing two hydrogen atoms bonded to silicon atoms per molecule at both ends of its chain, and having a dynamic viscosity at 25° C. of more than 200 mPa·s and 5,000 mPa·s or less. According to the above embodiment, the ratio of the number of moles of Si-H groups provided by component (c1) to the number of moles of Si-H groups provided by component (c2) is preferably 2:(1-10), in particular 1:(1-5).

[0028] In the present disclosure, component (c) provides 0.6 to 1.0 moles of Si-H groups per mole of total silicon-bonded alkenyl groups in components (a) and (b).

[0029] Component (c) is suitably used in an amount of from 30% to 70% by weight, for example from 40% to 60% by weight, based on the total weight of the composition.

[0030] <Ingredient (d)> Component (d) can be any of the various hydrosilylation catalysts used in the prior art to add cure silicone compositions, preferably platinum-based catalysts, such as chloroplatinic acid, chloroplatinic acid salts, platinum olefin complexes, and platinum alkenylsiloxane complexes.Platinum-based catalysts can be used in amounts subject to desired cure speed and economic considerations, which is usually the minimum level required to ensure effective hydrosilylation reaction.Generally, the weight of platinum metal in the siloxane composition is 0.1-500 ppm, for example 1-100 ppm.

[0031] <Ingredient (e)> The polyorganosiloxane (e) contains at least three hydrogen atoms bonded to silicon atoms per molecule and may be linear, cyclic, branched or resinous. The linear or cyclic polyorganosiloxane (e) is typically represented by the formula: R 2 3SiO 1 / 2 , H.R. 2 SiO 2 / 2 , H.R. 2 2SiO 1 / 2 and R 2 2SiO 2 / 2 (In the formula, R 2 The branched or resinous polyorganosiloxane (e) is composed of units selected from HSiO 3 / 2 and R 2 SiO 3 / 2 and / or SiO 4 / 2 wherein R 2 is as defined above.

[0032] The siloxane composition of the present disclosure does not contain polyorganosiloxane (e). By "free", it is meant that the polyorganosiloxane (e) is present in an amount of 0.01% by weight or less, or even 0.001% by weight or less, based on the total weight of the composition.

[0033] <Component (f)> The siloxane composition may further comprise an inhibitor (f) for controlling the pot life and curing rate of the composition. The inhibitor may be various inhibitors used in the art, such as alkynols, e.g., 1-ethynyl-1-cyclohexanol, 2-methyl-3-butyn-2-ol, polymethylvinylcyclosiloxanes, e.g., 1,3,5,7-tetravinyltetramethyltetracyclo-siloxane, alkyl maleates. The amount of the inhibitor may be selected according to its chemical structure and the desired curing rate. Generally, the weight of the inhibitor in the composition is 1 to 50,000 ppm, e.g., 10 to 10,000 ppm.

[0034] <Other optical components> The siloxane composition may further contain a filler if necessary. Examples of fillers include, but are not limited to, non-thermal conductive fillers such as calcium carbonate, fumed silica, precipitated silica, silica powder, diatomaceous earth, zirconium silicate, organic montmorillonite, titanium dioxide, and thermal conductive fillers such as aluminum oxide, zinc oxide, magnesium oxide, aluminum hydroxide, aluminum nitride, boron nitride, silicon carbide, aluminum, copper, nickel, gold, silver, graphite, graphene, and the like. As known in the art, the siloxane composition used as adhesive, sealant or protectant or potting material for electronic components can contain a suitable amount of filler. However, the siloxane composition used as potting material or optical adhesive material for display must not contain filler due to the requirement of light transmittance.

[0035] The siloxane composition may contain other additives in appropriate amounts, provided that the effect of the present invention is not impaired. Examples of such additives include, but are not limited to, solvents, diluents, fillers, and surface treatment agents for color pastes. Examples of solvents mentioned are decamethylcyclopentasiloxane, hexamethyldisiloxane, octamethyltrisiloxane, heptamethylhexyltrisiloxane, decamethyltetrasiloxane, dodecamethylpentasiloxane, tetradecamethylhexasiloxane, and isododecane. Examples of diluents to be measured are dimethyl silicone oil having a dynamic viscosity of 10 to 5,000 mPa·s at 25°C, and MDT silicone oil having a dynamic viscosity of 15 to 300 mPa·s at 25°C. Preferably, the composition does not contain any of the aforementioned additives. By "free," it is meant that the siloxane composition contains less than 0.1% by weight, or even less than 0.01% by weight, of the aforementioned additives, based on the total weight of the composition.

[0036] In a preferred embodiment, the siloxane composition comprises: (a) 20 to 70% by weight of at least one organopolysiloxane containing, per molecule, two alkenyl groups bonded to silicon atoms at both chain ends; (b) 1 to 10 weight percent of at least one organopolysiloxane containing at least three alkenyl groups bonded to silicon atoms per molecule; (c) 30 to 70% by weight of at least one organopolysiloxane containing, per molecule, two hydrogen atoms bonded to silicon atoms at each end of the chain, and (d) at least one hydrosilylation catalyst.

[0037] Suitably, the siloxane composition of the present disclosure is stored as two or more separate packages, where component (b), component (c) and component (d) are not stored in the same package, and where component (a), component (c) and component (d) are not stored in the same package.

[0038] The siloxane composition of the present disclosure preferably has a viscosity of 200 to 10,000 mPa·s, for example 500 to 5,000 mPa·s, particularly 500 to 2,000 mPa·s, at room temperature (23±2)° C. In this specification, viscosity refers to the mixed viscosity of the composition before curing. When the composition is stored in two or more separate packages, viscosity also refers to the viscosity of each package.

[0039] A second aspect of the present disclosure provides a silicone gel cured from the siloxane composition of the first aspect of the present disclosure.

[0040] This can be achieved by crosslinking or curing the composition described in the first aspect of the present disclosure, or by mixing separate packages as described above, followed by crosslinking or curing. Generally, crosslinking or curing is carried out at a temperature of 15-180°C for 10 minutes to 72 hours. Lower curing temperatures and shorter curing times are desirable. Curing at a temperature of 20-80°C for 15-120 minutes is preferred.

[0041] The silicone gel preferably has a penetration value of 20-50 as measured with a ¼ cone according to ASTM D1403.

[0042] A third aspect of the present disclosure provides the use of the siloxane composition of the first aspect as an adhesive, sealant or protectant for electronic components.

[0043] The cured siloxane composition of the present disclosure is in the form of a gel, has excellent breaking elongation, deformability and conformability, and can be used as an adhesive, sealant or protectant for electronic components, including, but not limited to, circuit boards, CPUs, and mobile phones.

[0044] A fourth aspect of the present disclosure provides the use of the siloxane composition of the first aspect as a potting material for an electronic component or display.

[0045] The siloxane composition of the present disclosure has low viscosity and good flowability, facilitating the operation for potting pressure sensors, metering sensors, insulated gate bipolar transistors, and displays, especially large displays such as large educational displays, outdoor displays, large touch screens, and touch automotive, navigation or aviation displays. In this specification, large displays generally refer to displays having a size of 50 inches or more, even 86 inches or more.

[0046] The siloxane composition of the present disclosure is used to fill the gap between a large display and a glass panel, and expels the air in the gap to make the display anti-reflective. In addition, the cured siloxane composition of the present disclosure is a gel with low permeability, and has excellent adhesion, light transmission, and negative pressure resistance, making it suitable for potting displays at high altitudes.

[0047] A fifth aspect of the present disclosure provides the use of the siloxane composition of the first aspect as an optical adhesive material for a display.

[0048] The cured siloxane composition of the present disclosure is in the form of a gel, and has excellent breaking elongation, deformability, conformability, adhesion, and light transmittance, and can be used as an optical adhesive material for displays, especially large displays. In addition, the cured gel has low permeability and excellent resistance to negative pressure, making it suitable for optical adhesion at high altitudes. [Brief description of the drawings]

[0049] [Figure 1] 1 shows adhesion test curves of the silicone gels obtained in Examples 1 and 2 and Comparative Examples 1 and 2. EXAMPLES

[0050] The present invention is further illustrated by the following examples, but is not limited in scope. Any experimental methods not specified in the following examples are selected according to conventional methods and conditions, or product specifications.

[0051] <Viscosity measurement> The viscosities of Components A and B were measured by a Brookfield viscometer using a No. 03 spindle at a speed of 10 rpm at room temperature (23±2° C.).

[0052] <Measurement of penetration> This was done according to ASTM D1403 with a 9.38 g ¼ scale cone at room temperature (23±2) °C. The samples to be tested shall have a diameter of 35 mm or more and a depth of 30 mm or more. Before the test, each siloxane composition was poured into a flat-bottom glass dish and cured at 65 °C for 30 minutes. The glass dish with the sample to be tested was then placed on the platform of the penetrometer, which was adjusted and fixed in the appropriate position by a crane, after which the rod connecting the cone was slowly lowered by the handle until it was observed through the mirror that the cone tip had touched the surface of the sample. The standard cone was then released to fall under its own weight for 10 seconds after zero setting, penetrating the sample and its depth was recorded by the displacement indicator. The same sample was tested at least three times in parallel, and the distance between each test point and the edge of the glass dish should not be less than 10 mm. The standard cone must be replaced with a clean one for each test or wiped with cotton or cloth soaked in alcohol. The average of each test was taken as the result.

[0053] <Shore hardness A measurement> This was done in accordance with standard GB / T531-1999.

[0054] <Adhesiveness measurement> This was measured by a texture analyzer using a P / 25 cone. Prior to testing, a flat-bottom glass dish (with a diameter of 35 mm and a depth of 30 mm) was filled with the siloxane composition and subjected to 65°C for 30 minutes. The glass dish with the sample to be tested was then placed directly under the test cone, after which the texture analyzer was turned on and the test cone was lowered to the surface of the sample at a speed of 2 mm / sec until the test cone penetrated the sample to a depth of 2 mm. The test cone was then left stationary for 5 seconds to completely wet the sample, and then moved upwards at a speed of 2 mm / sec until the sample was separated therefrom. The force was recorded by a sensor along with the time the test cone penetrated and was pulled out of the sample. The adhesion of the sample can be evaluated by the area under and enclosed by the time axis by the force-time curve. The larger the area, the better the adhesion.

[0055] <High temperature test> Each component A and B was mixed in a static mixer in a 1:1 ratio, and the resulting mixture was applied to a polarizing plate of an 80-inch display in the form of a fishbone diagram, and then a glass panel was lightly placed on top of it. No air bubbles should be generated during the entire process. The product was then subjected to 65°C for 30 minutes, and then left at room temperature for 3 days, and then placed in a 95°C oven for 200 hours. If no air bubbles or peeling were observed, or no separation between the gel and the polarizing plate or glass panel occurred after being placed at 95°C for 200 hours, the product was judged to have passed the high temperature test.

[0056] <Negative pressure test> Each component A and B was mixed in a static mixer in a 1:1 ratio, and the resulting mixture was applied to a polarizing plate of a 14-inch display in the form of a fishbone diagram, and then a glass panel was lightly placed on top of it. No air bubbles should be generated during the entire process. The product was then subjected to 65°C for 30 minutes, and then left at room temperature for 3 days, and then placed in an environment of -1 atmosphere for 3 days. After being placed at -1 atmosphere for 3 days, if no air bubbles or peeling were observed, or no separation occurred between the gel and the polarizing plate or glass panel, the product was judged to have passed the negative pressure test.

[0057] Details of the raw materials used in the examples and comparative examples are as follows.

[0058] a1: a dimethylvinylsiloxy-terminated polydimethylsiloxane having a dynamic viscosity of approximately 1,000 mPa·s at 25°C and a vinyl content of 0.124 mmol / g, supplied by Wacker Chemicals.

[0059] a2: a dimethylvinylsiloxy-terminated polydimethylsiloxane having a dynamic viscosity of approximately 20,000 mPa·s at 25°C and a vinyl content of 0.042 mmol / g, supplied by Wacker Chemicals.

[0060] b1: A vinyl MQ resin having a molar ratio of M to Q units of 0.7:1 and a vinyl content of 0.78 mmol / g, supplied by Wacker Chemicals.

[0061] b2: a trimethylsiloxy-terminated polydimethylsiloxane having multiple vinyl groups bonded to silicon atoms in the side chains, with a dynamic viscosity of about 340-820 mPa·s at 25 °C and a vinyl content of 2.8 mmol / g, supplied by Wacker Chemicals.

[0062] c1: A dimethylhydrosiloxy-terminated polydimethylsiloxane having a dynamic viscosity of about 65 mPa·s at 25°C and a hydrogen content of 0.53 mmol / g, supplied by Wacker Chemicals.

[0063] c2: A dimethylhydrosiloxy-terminated polydimethylsiloxane having a dynamic viscosity of about 1,000 mPa·s at 25°C and a hydrogen content of 0.12 mmol / g, supplied by Wacker Chemicals.

[0064] c3: A dimethylhydrosiloxy-terminated polydimethylsiloxane having a dynamic viscosity of about 15 mPa·s at 25°C and a hydrogen content of 1.8 mmol / g, supplied by Wacker Chemicals.

[0065] d: Platinum-based catalyst, WACKER® CATALYST EP, supplied by WACKER Chemicals.

[0066] e: Trimethylsiloxy-terminated polydimethylsiloxane with multiple hydrogen atoms bonded to silicon atoms in the side chains, having a dynamic viscosity of 150 mPa·s at 25 °C and a hydrogen content of 1.8 mmol / g, supplied by Wacker Chemicals.

[0067] f: Inhibitor supplied by Wacker Chemicals, WACKER® INHIBITOR PT88.

[0068] g: Methyl MQ resin, WACKER® MQ803, supplied by Wacker Chemicals.

[0069] [Examples 1-2 and Comparative Examples 1-3] The components of each of components A and B were thoroughly mixed according to the formulation in Table 1. Components A and B were then mixed together, and the resulting mixture was cured at 65° C. for 30 minutes to obtain a silicone gel.

[0070] The penetration values ​​of the silicone gels obtained in each of the Examples and Comparative Examples are shown in Table 2. In Comparative Example 3, silicone rubber was obtained instead of silicone gel, so the Shore hardness A was measured.

[0071] Fig. 1 shows the adhesion test curves of the silicone gels obtained by Examples 1-2 and Comparative Examples 1-2. It can be seen that the one derived from Example 1 shows excellent adhesion, that of Example 2 shows good adhesion, but that of Comparative Examples 1-2 shows significantly worse adhesion than that of Examples 1-2. The silicone rubber obtained in Example 3 did not have adhesion, and the corresponding test was not carried out.

[0072] Table 3 shows the test results under high temperature and negative pressure for the silicone gels obtained in Examples 1-2 and Comparative Examples 1-2. Comparative Example 1 failed both tests because air bubbles or peeling were observed after the tests. Comparative Example 2 also failed both tests because separation between the gel and the polarizing plate or glass panel was observed after the tests.

[0073] [Table 1]

[0074] [Table 2]

[0075] [Table 3]

Claims

1. 1. A siloxane composition comprising: (a) at least one organopolysiloxane containing, per molecule, two alkenyl groups bonded to silicon atoms at each end of the chain; (b) at least one organopolysiloxane containing at least three alkenyl groups bonded to silicon atoms per molecule; (c) at least one organopolysiloxane containing two hydrogen atoms bonded to silicon atoms per molecule at each end of the chain; and (d) at least one hydrosilylation catalyst; with the proviso that component (c) is used in an amount of 30 weight percent or more, based on the total weight of the composition, and the composition comprises 0.01 weight percent or less, based on the total weight of the composition, of component (e) of at least one organopolysiloxane containing at least 3 hydrogen atoms bonded to silicon atoms per molecule, or does not comprise component (e); Component (c) has a dynamic viscosity at 25°C of 30 mPa·s or more and less than 1,000 mPa·s, Component (c) is (c1) an organopolysiloxane having a dynamic viscosity at 25° C. of 30 mPa·s or more and 200 mPa·s or less, and containing two hydrogen atoms bonded to silicon atoms per molecule at both ends of the chain; and (c2) an organopolysiloxane having a dynamic viscosity at 25° C. of more than 200 mPa·s and not more than 5000 mPa·s, and containing two hydrogen atoms bonded to silicon atoms per molecule at both ends of the chain; Siloxane compositions.

2. 10. The siloxane composition of claim 1, wherein component (c) is used in an amount of 40 weight percent or greater, based on the total weight of the composition.

3. The siloxane composition according to claim 1 or 2, wherein the ratio of the number of moles of Si-H groups provided by component (c1) to the number of moles of Si-H groups provided by component (c2) is 2:(1 to 10).

4. The siloxane composition of any one of claims 1 to 3, wherein component (c) provides from 0.6 to 1.0 moles of Si-H groups per mole of total silicon-bonded alkenyl groups in components (a) and (b).

5. The siloxane composition of any one of claims 1 to 4, wherein component (b) is selected from the group consisting of: (b1) Essentially R 1 R 2 2 SiO 1/2 Units and SiO 4/2 An organopolysiloxane comprising units (b2) Essentially R 2 3 SiO 1/2 Units and R 1 R 2 SiO 2/2 An organopolysiloxane comprising units (b3) Essentially R 1 R 2 2 SiO 1/2 Units, R 1 R 2 SiO 2/2 Units and R 2 2 SiO 2/2 An organopolysiloxane consisting of units, and (b4) Essentially R 1 R 2 2 SiO 1/2 , R 2 2 SiO 2/2 Units and R 2 SiO 3/2 Organopolysiloxane consisting of units [In the formula, R 1 is independently in each occurrence an alkenyl group having 2 to 6 carbon atoms; R 2 is independently in each occurrence a monovalent hydrocarbon radical free of aliphatic unsaturation having 1 to 20 carbon atoms.

6. The siloxane composition of any one of claims 1 to 5, wherein component (a) comprises: (a1) an organopolysiloxane having a dynamic viscosity at 25° C. of 100 mPa·s or more and less than 5,000 mPa·s, and containing two alkenyl groups bonded to silicon atoms per molecule at both chain ends; (a2) An organopolysiloxane having a dynamic viscosity at 25° C. of 5,000 mPa·s or more and 50,000 mPa·s or less, which contains two alkenyl groups bonded to silicon atoms per molecule at both chain ends.

7. The siloxane composition of any one of claims 1 to 6, comprising: (a) from 20 to 55 percent by weight of at least one organopolysiloxane containing, per molecule, two alkenyl groups bonded to silicon atoms at each chain end; (b) from 1 to 10 percent by weight of at least one organopolysiloxane containing at least three alkenyl groups bonded to silicon atoms per molecule; (c) 30 to 70% by weight of at least one organopolysiloxane containing, per molecule, two hydrogen atoms bonded to silicon atoms at each end of the chain; and (d) at least one hydrosilylation catalyst.

8. A silicone gel cured from the siloxane composition according to any one of claims 1 to 7.

9. 9. The silicone gel of claim 8, characterized by a penetration value of 20 to 50 measured with a 1 / 4 cone according to ASTM D1403.

10. Use of the siloxane composition according to any one of claims 1 to 7 as a potting material.

11. The use according to claim 10, wherein the siloxane composition is used as a potting material for a display.

12. Use of the siloxane composition according to any one of claims 1 to 7 as an optical adhesive material.

13. The use according to claim 12, wherein the siloxane composition is used as an optical adhesive material for a display.

Citation Information

Patent Citations

  • Silicone skin adhesive gels

    EP1737504A1

  • Addition curable organopolysiloxane composition and semiconductor device

    JP2017039885A

  • Curable silicone gel composition

    JP2018076407A

  • Organopolysiloxane composition for forming pressure sensitive adhesive layer and use of same

    WO2019009175A1

  • Silicone adhesive composition and use thereof

    WO2020121930A1